2008
DOI: 10.1111/j.1523-536x.2007.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Reports of Postpartum Pain Associated with Vaginal and Cesarean Deliveries: Results of a National Survey

Abstract: Background: As cesarean rates increase worldwide, a debate has arisen over the relationship of method of delivery to maternal postpartum physical health. This study examines mothers' reports of their postpartum experiences with pain stratified by method of delivery. Methods: Listening to Mothers II was a survey of a total of 1,573 (200 telephone and 1,373 online) mothers aged 18 to 45 years, who had a singleton, hospital birth in 2005. They were interviewed by the survey research firm, Harris Interactive, in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
143
0
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(161 citation statements)
references
References 28 publications
5
143
0
13
Order By: Relevance
“…The study reported puerperal complaints regarding episiotomy after spontaneous vaginal delivery. In multiparous women, associations were observed with intestinal problems (p=0.001), perineal pain (p<0.001), perineal infection (p<0.001) and interference of pain in daily activities (p<0.001) (4) . Considerable variation is found in episiotomy rates, although the World Health Organization (5) recommends its limited use in about 10% of normal deliveries.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The study reported puerperal complaints regarding episiotomy after spontaneous vaginal delivery. In multiparous women, associations were observed with intestinal problems (p=0.001), perineal pain (p<0.001), perineal infection (p<0.001) and interference of pain in daily activities (p<0.001) (4) . Considerable variation is found in episiotomy rates, although the World Health Organization (5) recommends its limited use in about 10% of normal deliveries.…”
Section: Introductionmentioning
confidence: 98%
“…A large-scale survey, carried out two months after birth, revealed that most of the women submitted to instrumental delivery mentioned perineal pain, 77% of whom were primiparous and 52% multiparous, and that 31% of the 73% of primiparous women after spontaneous vaginal delivery had an episiotomy (4) . Pharmacological and non-pharmacological treatments have been investigated for perineal pain control after vaginal delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a US national survey of postpartum women indicate that seventy nine percent of women following a caesarean delivery experienced pain at the incision in the first 2 months after birth, with thirty three percent describing it as a major problem, and eighteen percent reported persistence of the pain into the sixth month postpartum [7]. The purpose of this study was to describe women's experience following childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 A principal queixa encontrada na população estudada foi a dor, referida principalmente na região dos pontos -episiotomia nos casos de parto vaginal e incisão cirúrgica das cesáreas -, o que corrobora estudos anteriores, que demonstram que tanto parturientes de parto vaginal como de parto cesáreo apresentam dor na região dos pontos, com a diferença de que a duração da dor é menor no parto vaginal quando comparado ao parto cesáreo. 16,17 A segunda queixa mais frequente na avaliação foi có-lica, considerando que a maioria das puérperas apresentou involução uterina dentro da normalidade, ou seja, em regiões próximas à cicatriz umbilical. Isso ocorre pois o estímulo da amamentação, provocado pela sucção do bebê, promove liberação de ocitocina, que parece acentuar essa dor por promover contrações uterinas.…”
Section: Discussão E Conclusãounclassified